Digital Transformation of Ship Administrative Systems to Enhance Operational Efficiency in Maritime Education Institutions - Umasangadji, Fahmi; Sutrisno, Imam (International Journal of Marine Engineering Innovation and Research, 2026)
The management of ship administrative systems in maritime education institutions remains predominantly manual, fragmented, and vulnerable to documentation errors, certification lapses, and operational inefficiencies. As training vessels serve both educational and operational functions, ineffective administrative processes may disrupt academic activities, regulatory compliance, and maintenance scheduling. This study aims to design and evaluate a digital ship administrative management system to enhance operational efficiency and regulatory compliance in maritime education institutions. The research adopts a system development approach consisting of requirement analysis, system architecture design, prototype development, and performance evaluation. The proposed system integrates digital certificate monitoring, automated expiry notifications, document tracking, and a centralized dashboard for real-time administrative status monitoring. System performance is evaluated using operational efficiency indicators, including document processing time, error reduction rate, and administrative readiness level. The results demonstrate that the implementation of the digital administrative system significantly improves document accessibility, reduces processing delays, and enhances compliance monitoring. The centralized dashboard enables proactive decision-making and minimizes the risk of certification expiration. This study contributes to maritime engineering management by providing a practical digital transformation framework tailored for maritime education institutions, supporting the transition toward smart maritime governance and Industry 4.0 practices.